Evaluation of an anti-diuretic activity of fluvoxamine in albino rats - Firdose, Nagma; Suresha, R. N.; Sibgatullah, Mohammed; Bashir, Sabreen; Poornima, R.; Reddy, Divya (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Diabetes insipidus is a disease characterized by high amounts of urine excretion. Antidiuretic drugs are used to treat this condition. Hence, our study intends to evaluate the anti-diuretic effect of fluvoxamine, a selective serotonin reuptake inhibitors in albino rats. Methods: Albino rats were divided into three groups of six animals each. The control group was fed with distilled water 10 ml/kg body weight, standard group received 4 units of vasopressin and test group received fluvoxamine 18 mg/kg body weight. On the day of experiment, diuresis was induced in all the groups by giving frusemide in a dose of 20 mg/kg body weight after loading with saline at 25 ml/kg body weight. The animals were confined in diuretic cage for a period of 5 hrs and urine output was noted. Urine was analyzed for electrolyte concentration (Na+, K+, Cl−). Results: There was significant reduction in urine output in the test group of animals when compared to the control group. Electrolyte concentration revealed relatively concentrated urine when compared to the control group. Conclusions: Fluvoxamine has a significant anti-diuretic action in the albino rats.